Utilization of corn gluten meal as a protein source in great sturgeon (Huso huso) diets in growth up stage - Sayed Hassani, M.H.; Mohseni, M.; Yazdani Sadati, M.A.; Pourali, H.M.; Shakorian, M. (2014)
The utilization of corn gluten meal (CGM) was evaluated as a replacement for fish meal (FM) in practical diets for beluga Huso huso in growth up stage. Four experimental diets (isonitrogenus and isocaloric , 40 % protein and 18 kj/ g diet) were formulated. Fish meal was replaced by CGM at 0%, 20%, 40% and 60% being named as CGM0, CGM20, CGM40 and CGM60, respectively. Fingerlings great sturgeon with an initial body weight of ± 78.876.94gr (mean ±SD) were reared in 12 fiberglass tanks and fed with diets for10 weeks at 20.00± 2 oC. At the end of experiment, growth performance (final weight, body increase weight, specific growth rate) of fish fed CGM20 and CGM40 were significantly higher than fish fed control diet, While feed conversion ratio were lower than fish fed CGM40 and CGM60 compared with control diet. There were not significant difference in condition factor, protein efficiency ratio and body protein in different experimental groups , but body lipid increased as dietary gluten meal increased (P<0.05). Different levels of corn gluten meal did no significantly affect Aspartat amino transferas (AST), Alanin amino transferas (ALT) and Triglyceride, but amount of cholesterol in fish fed diets CGM40 and CGM 60 were significantly lower than control diet (P<0.05). The present study revealed that CGM is a suitable source as replacement with fish meal and might be included in great sturgeon commercial diet up to 60 % with no adverse effect on nutrition efficiency, liver enzymes and biochemical parameters.